The Old English Translation of Bede's Historia Ecclesiastica Gentis Anglorum in its Historical and Cultural Context - Lemke, Andreas (Universitätsverlag Göttingen, 2015)
Did King Alfred the Great commission the Old English translation of Bede's Historia Ecclesiastica Gentis Anglorum, probably the masterpiece of medieval Anglo-Latin Literature, as part of his famous program of translation to educate the Anglo-Saxons? Was the Old English Historia, by any chance, a political and religious manifesto for the emerging 'Kingdom of the Anglo-Saxons'? Do we deal with the literary cornerstone of a nascent English identity at a time when the Anglo-Saxon kingdoms were threatened by a common enemy: the Vikings? Andreas Lemke seeks to answer these questions - among others - in his recent publication. He presents us with a unique compendium of interdisciplinary approaches to the subject and sheds new light on the Old English translation of the Historia in a way that will fascinate scholars of Literature, Language, Philology and History.